Recovery of visual function after endarterectomy - series of cases report - Krasińska-Płachta, Aleksandra; Brązert, Agata; Mamczur-Załęcka, Joanna; Begier-Krasińska, Beata; Krasiński, Zbigniew; Kocięcki, Jarosław (Journal of Education, Health and Sport, 2023)
Carotid arteriosclerosis is the main cause of the stroke but it can also lead to ophthalmic symptoms. In this article, we aim to present four patients. All of them had hemodynamically significant but asymptomatic unilateral carotid stenosis and underwent internal carotid endarterectomy. Postoperatively, their visual function improved. Mean deviation in perimetry and values of amplitudes in pattern visual evoked potentials increased. Two patients improved visual acuity; in the other two, it remained stable.